Critical Thinking in Nurses: Predictive Role of Emotional Intelligence - Zahra Madadkhani; Mansoureh Nikoogoftar (Tehran University of Medical Sciences, 2015)
Background & Aim: Critical thinking is a necessary and important component of nursing profession. Since nurses are not limited to work under predetermined roles and need to meet various needs of patients, they should have critical thinking skills. This study aimed to determine the role of emotional intelligence and its components in critical thinking disposition .   Methods & Materials: In this cross-sectional study, 118 female nurses working in educational hospitals of Qazvin were selected using quota sampling method. They completed the Trait Metal Mood Scale (TMMS) and the California Critical Thinking Disposition Inventory (CCTDI). Data were analyzed using descriptive statistics (frequency, mean, standards deviation and Pearson correlation coefficient) and inferential statistics (Multiple Regression) in the SPSS-16 .    Results: The results showed that there was a significant positive correlation between the total score of emotional intelligence with the total score of disposition toward critical thinking (r=0.385). There were also positive relationships between the total score of disposition toward critical thinking with the two subscales of emotional clarity (r=0.459) and emotional healing (r=0.220). There was no statistically significant relationship between the subscale of attention to emotion and total critical thinking score (r=0.117). The subscale of emotional clarity significantly predicted 21% of changes in critical thinking .   Conclusion: Nurses who were more aware of their emotions and emotional transparency had higher critical thinking tendency. Empowering critical thinking can directly affect patients' conditions. Given the major role of emotional intelligence in critical thinking, teaching nurses such skills could result in better performance and improving the quality of nursing care.